Square-Planar Heteroleptic Complexes of α-Diimine-NiII-Catecholate Type: Intramolecular Ligand-to-Ligand Charge Transfer - Kira I. Pashanova; Vladlena O. Bitkina; Ilya A. Yakushev; Maxim V. Arsenyev; Alexandr V. Piskunov (Molecules, 2021)
Two heteroleptic NiII complexes combined the redox-active catecholate and 2,2′- bipyridine ligand platforms were synthesized to observe a photoinduced intramolecular ligand-to-ligand charge transfer (LL’CT, HOMOcatecholate → LUMOα-diimine). A molecular design of compound [NiII(3,6-Cat)(bipy)]∙CH3CN (1) on the base of bulky 3,6-di-tert-butyl-o-benzoquinone (3,6-DTBQ) was an annelation of the ligand with an electron donor glycol fragment, producing derivative [NiII(3,6-Catgly)(bipy)]∙CH2Cl2 (2), in order to influence the energy of LL’CT transition. A substantial longwave shift of the absorption peak was observed in the UV-Vis-NIR spectra of 2 compared with those in 1. In addition, the studied NiII derivatives demonstrated a pronounced negative solvatochromism, which was established using a broad set of solvents. The molecular geometry of both compounds can be ascribed as an insignificantly distorted square-planar type, and the π–π intermolecular stacking of the neighboring α-diimines is realized in a crystal packing. There is a lamellar crystal structure for complex 1, whereas the perpendicular T-motifs with the inter-stacks attractive π–π interactions form the packing of complex 2. The redox-active nature of ligand systems was clearly shown through the electrochemical study: a quasi-reversible one-electron reduction of 2,2′-bipyridine and two reversible successive one-electron oxidative conversations (“catecholate dianion—o-benzosemiquinonato radical anion—neutral o-benzoquinone”) were detected.